Surveillance of Avian Paramyxovirus in Migratory Waterfowls in the San-in Region of Western Japan from 2006 to 2012 - UMALI, Dennis V. (The Japanese Society of Veterinary Science, 2013)
Relatively little is known about the distribution of avian paramyxoviruses (APMVs) among wild birds in Japan. Surveillance of APMV in migratory waterfowl was conducted in the San-in region of western Japan during winters of 2006 to 2012. A total of 16 avian paramyxoviruses consisting of 3 lentogenic Newcastle disease viruses (NDVs), 12 APMV-4 and 1 APMV-8 were isolated from 1,967 wild-bird fecal samples. The results show that NDV and APMV-4 are relatively widely distributed among wild waterfowl that migrate to Japan from northern regions. Phylogenetic analysis revealed that there was no genetic relationship between the isolates from wild birds and domestic poultry in Japan. However, surveillance of APMVs in wild waterfowl needs to be conducted due to the pathogenic potential of these isolates in domestic poultry.